The fuzzy PD control for combined energy and attitude control system - Aslam, Sohaib; Yew, Chung Chak; Jaffery, Mujtaba Hussain; Varatharajoo, Renuganth (Emerald, 2022)
Purpose: The satellite pointing accuracy plays a crucial role in ensuring a successful satellite mission itself. Therefore, this paper aims to enhance the attitude pointing accuracy of the combined energy and attitude control system (CEACS) in a satellite in the presence of external disturbance torques through a robust controller, which can produce high pointing accuracies with smaller control torques. Design/methodology/approach: To improve the CEACS attitude pointing accuracy, a maiden fuzzy proportional derivative (PD)-based CEACS architecture is proposed. The mathematical models along with its numerical treatments of the fuzzy PD-based CEACS attitude control architecture are presented. In addition, a comparison between the PD and fuzzy PD controllers in terms of the CEACS pointing accuracies and control torques is provided. Findings: Numerical results show that the fuzzy PD controller produces a considerable CEACS pointing accuracy improvement for a lower control torque compartment. Practical implications: CEACS has gained a renew interest because of significant increase in the projected onboard power requirements for future space missions. Therefore, it is of paramount importance to improve the CEACS pointing accuracy itself with a minimum control torque compartment. In fact, this proposed fuzzy PD controller is shown to be a potential CEACS attitude controller. Originality/value: The fuzzy PD-based CEACS architecture not only provides a better attitude pointing accuracy but also ensures a lower control torque compartment, which corresponds to a lower onboard power consumption.